2014
DOI: 10.1063/1.4873678
|View full text |Cite
|
Sign up to set email alerts
|

Laser-generated ultrasound with optical fibres using functionalised carbon nanotube composite coatings

Abstract: Optical ultrasound transducers were created by coating optical fibres with a composite of carbon nanotubes (CNTs) and polydimethylsiloxane (PDMS). Dissolution of CNTs in PDMS to create the composite was facilitated by functionalisation with oleylamine. Composite surfaces were applied to optical fibres using dip coating. Under pulsed laser excitation, ultrasound pressures of 3.6 MPa and 4.5 MPa at the coated end faces were achieved with optical fibre core diameters of 105 and 200 μm, respectively. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 19 publications
3
109
0
3
Order By: Relevance
“…The methods for creating this material and applying it to the optical fiber end face were previously described [12]. Briefly, the composite was created by mixing functionalised CNTs, xylene and PDMS.…”
Section: Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods for creating this material and applying it to the optical fiber end face were previously described [12]. Briefly, the composite was created by mixing functionalised CNTs, xylene and PDMS.…”
Section: Setupmentioning
confidence: 99%
“…Recent studies have highlighted the efficacy of composite materials that comprise optical absorbers integrated within elastomers [5,10,11]. The authors recently demonstrated a method for creating ultrasound transmitters at the tip of an optical fiber using a composite material comprised of functionalised multi-walled carbon nanotubes (CNTs) and polydimethylsiloxane (PDMS) [12]. Using optical fibers with 200 µm core diameters, ultrasound pressures of 4.5 MPa were achieved, with corresponding bandwidths of 15 MHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…따라서 오래 전부터 산모와 태아를 진단하는 데 널리 사용되고 있으 며 근래에는 일반 환자의 체내 근육, 힘줄, 장기들의 크기와 구조들을 단층영상으로 가시화하는데 사용되고 있다 [3] . [4] , 금속 미세패턴 (Au nanoparticle) [5] 또는 CNT (carbon nanotube)를 PDMS (Polydimethylsiloxane)와 혼합하는 방법에 기반하고 있다 [6][7][8][9] . …”
Section: 서 론unclassified
“…As previously described in Refs. [14,15], the coating comprised multi-walled carbon nanotubes as optical absorbers and polydimethylsiloxane (PDMS) as an elastomeric host. The coating was applied to the distal end of an optical fibre (core diameter: 200 μm) with dip coating.…”
Section: Ultrasonic Tracking Systemmentioning
confidence: 99%